Begonia subvillosa, new running wild Begonia in Cibodas Botanical Gardens and naturalized prediction - Muhammad Efendi; Abidin Ibrahim; Yani Suryani; Salma Salsabila (Biogenesis: Jurnal Ilmiah Biologi, 2022)
.